Conversion, crisis, and growth : the religious management of change within the St John's Apostolic Faith Mission and the Reformed Presbyterian Church in Cape Town, South Africa - Masondo, Sibusiso Theophilus (Department of Religious Studies, 2014)
Bibliography: p. 229-245.